2021
DOI: 10.1038/s41598-021-95300-3
|View full text |Cite
|
Sign up to set email alerts
|

White matter tracts characteristics in habitual decision-making circuit underlie ritual behaviors in anorexia nervosa

Abstract: Anorexia nervosa (AN) is a difficult to treat, pernicious psychiatric disorder that has been linked to decision-making abnormalities. We examined the structural characteristics of habitual and goal-directed decision-making circuits and their connecting white matter tracts in 32 AN and 43 healthy controls across two independent data sets of adults and adolescents as an explanatory sub-study. Total bilateral premotor/supplementary motor area-putamen tracts in the habit circuit had a significantly higher volume i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 53 publications
1
25
1
Order By: Relevance
“…With regard to the habit tract, we found no significant differences in myelin density, neurite density, or neurite orientation in those with AN. In a previous examination of SMA-toputamen tracts in a partially overlapping cohort of adolescents with AN and controls, we similarly found no significant differences in FA (nor in white matter volume or number of streamlines) (25). The present study also did not find significant differences, despite including a larger sample and examining multiple indices of WM microstructure rather than gross volume and tract number (which should afford greater sensitivity to detect white matter abnormalities associated with specific clinical conditions (55)).…”
Section: White Matter Microstructural Findings In Reward Circuit Tractssupporting
confidence: 65%
“…With regard to the habit tract, we found no significant differences in myelin density, neurite density, or neurite orientation in those with AN. In a previous examination of SMA-toputamen tracts in a partially overlapping cohort of adolescents with AN and controls, we similarly found no significant differences in FA (nor in white matter volume or number of streamlines) (25). The present study also did not find significant differences, despite including a larger sample and examining multiple indices of WM microstructure rather than gross volume and tract number (which should afford greater sensitivity to detect white matter abnormalities associated with specific clinical conditions (55)).…”
Section: White Matter Microstructural Findings In Reward Circuit Tractssupporting
confidence: 65%
“…The current study, examining a different part of the reward circuit, showed an opposite direction of abnormalities: decreases in both the white matter integrity and functional connectivity during reward motivation in the VTA-to-NAcc connection. In a separate study, we found evidence in AN of increased structural connectivity (higher volume of white matter fibers compared with controls) in a habitual decision-making circuit consisting of tracts connecting the posterolateral putamen to the premotor/supplementary area ( 72 ). Further, there was a significant positive correlation between volume of white matter fibers and the severity of eating disorder-related ritualistic behaviors in the weight-restored AN cohort.…”
Section: Discussionmentioning
confidence: 82%
“…The current findings differ somewhat from prior investigations of region-to-region white matter connectivity. Two prior studies testing group differences in individual tracts reported stronger connectivity in intra-hemispheric frontostriatal tracts amongst individuals with AN, both between the nucleus accumbens and OFC (12, 55), and between the putamen and motor areas (13). These differences were not found in the current study, which could result from the unit of analysis here being constellations of connected white matter connections rather than individual tracts.…”
Section: Discussionmentioning
confidence: 95%
“…Several diffusion tractography studies of AN have been reported, but here too, there have been important limitations. Most notably, tractography studies of AN have been constrained by small sample sizes, and consistent findings across studies have not emerged (11-13). The single tractography study that had a relatively large sample (n= 96 AN and 96 HC (14)) used deterministic tractography, an approach that assumes that all white matter fibers within a voxel are oriented in the same direction.…”
Section: Introductionmentioning
confidence: 99%